2016
DOI: 10.1111/1541-4337.12200
|View full text |Cite
|
Sign up to set email alerts
|

Electrolyzed Water as a Novel Sanitizer in the Food Industry: Current Trends and Future Perspectives

Abstract: Electrolyzed water (EW) has gained immense popularity over the last few decades as a novel broad-spectrum sanitizer. EW can be produced using tap water with table salt as the singular chemical additive. The application of EW is a sustainable and green concept and has several advantages over traditional cleaning systems including cost effectiveness, ease of application, effective disinfection, on-the-spot production, and safety for human beings and the environment. These features make it an appropriate sanitizi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
218
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 299 publications
(238 citation statements)
references
References 134 publications
3
218
0
6
Order By: Relevance
“…The technology is based on electrolysis or the use of a direct electric current to drive a chemical reaction that would otherwise not occur. In the case of NEW, electrolysis of sodium chloride in water results in the pH-dependent production of chlorine oxidants, such as chlorine gas, hypochlorous acid, and hypochlorite ion (14). Electrolyzed water in its acidic, neutral, and alkaline forms has been shown to have antimicrobial effects against foodborne and hospital-acquired bacterial, viral, and parasitic pathogens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The technology is based on electrolysis or the use of a direct electric current to drive a chemical reaction that would otherwise not occur. In the case of NEW, electrolysis of sodium chloride in water results in the pH-dependent production of chlorine oxidants, such as chlorine gas, hypochlorous acid, and hypochlorite ion (14). Electrolyzed water in its acidic, neutral, and alkaline forms has been shown to have antimicrobial effects against foodborne and hospital-acquired bacterial, viral, and parasitic pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…HOCl is a more effective biocide relative to its dissociated form (OCl Ϫ ), which is the active ingredient of bleach. Manipulating the pH-dependent aqueous chemistry of electrolyzed water to a near neutral pH ensures that the HOCl Ϫ molecule predominates (14). Neutral electrolyzed water (NEW; pH 7) has been shown to be effective at reducing or eliminating bacterial pathogens (14) and cultivable human NoV surrogates, e.g., murine norovirus (15,16).…”
mentioning
confidence: 99%
“…However, the use of new technologies for the generation of chlorinated water, such as electrolysis, can make this process more practical, simple and environmentally appropriate (Rahman et al, 2016). Due to its minimal corrosive potential, SAEW may be less aggressive to human health and the environment, requiring minimum safety processes to manipulate it (Zacharia et al, 2010).…”
Section: Electrolyzed Watermentioning
confidence: 99%
“…The saline solution generates an electric current between the poles, and the changes in its concentration may generate different chlorine values available. With variations from 2 to 20 g/L of NaCl in pure water, it is possible to produce electrolyzed water with chlorine concentrations from 5 to 200 mg/L (Hsu, 2005;Rahman et al, 2016). The mixture of acidic electrolyzed water and basic electrolyzed water forms the SAEW, which has a pH between 6 and 6.5, oxidation-reduction potential (Eh) 800-900mV, containing predominantly HOCl (95%) and hypochlorite ions (ClO --5%) and traces of Cl 2 (Guentzel et al, 2008).…”
Section: Electrolyzed Watermentioning
confidence: 99%
“…Outbreaks are a global reality, and considered a public health problem of wide scope and have negative impacts on the productivity, economy and consumer confidence. According to Rahman et al (2016), the Centers for Disease Control and Prevention (CDC) have reported numerous different foodborne pathogens that can cause infections in humans. From 2013 to 2015, several Salmonella outbreaks were reported worldwide, with one outbreak per year attributed to the consumption of cucumbers contaminated with this pathogen in the USA (CDC, 2013;Angelo et al, 2015;CDC, 2015).…”
Section: Introductionmentioning
confidence: 99%